(untitled) (International Journal of Engineering and Computer Science, 2014)
An E-CIRCULAR SYSETEM consisting of code number was designed, and we are transmitting the data through wireless medium and data is displayed on the LCD display in the corresponding classroom or lecturer hall or some other places. The transmitter side is the principal room, and he can send the messages whatever he wants to inform to this college staff or student using pc or mobile and the transmitted message is received through the GSM modem. Then the received message is displayed on the LCD screen and at the same time alarm will be heard